Assessing the adoption level of scaled agile development: a maturity model for Scaled Agile Framework. Issue 6 (7th July 2016) - Turetken, Oktay; Stojanov, Igor; Trienekens, Jos J. M.
Abstract: Although the agile software development approaches have gained wide acceptance in practice, the concerns regarding the scalability and integration of agile practices in traditional large‐scale system development projects are prevailing. Scaled Agile Framework (SAFe) has emerged as a solution to address some of these concerns. Despite few encouraging results, case studies indicate several challenges of SAFe adoption. Currently, there is a lack of a well‐structured gradual approach for establishing SAFe. Before and during SAFe adoption, organizations can benefit greatly from a uniform model for assessing the current progress, and establishing a roadmap for the initiative. To address this need, we developed a maturity model that provides guidance for software developing organizations in defining a roadmap for adopting SAFe. The model can also be used to assess the level of SAFe adoption. We took an existing agile maturity model as a basis for agile practices and extended it with practices that are key to SAFe. The model was developed and refined with industry experts using the Delphi technique. A case study was conducted in a large organization where we evaluated the model by applying it to assess the level of SAFe adoption. © 2016 The Authors. Journal of Software: Evolution and Process Published by John Wiley & Sons Ltd. Abstract : Scaled Agile Framework (SAFe) has emerged as a solution to address some of the concerns regarding the scalability and integration of agile practices in large‐scale development projects. We developed a maturity model that provides guidance for software‐developing organizations in defining a roadmap and assessing the level of SAFe adoption. We took an existing agile maturity model as a basis, extended it with key SAFe practices, refined the model with industry experts using Delphi technique, and applied it in an enterprise.